How does the need for IVF affect pregnancy complications among multiple gestations? The study of a large American population database including almost 100,000 multiple gestations - Samar Mandourah; Ahmad Badeghiesh; Haitham Baghlaf; Michael H. Dahan (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2024)
Objective: This study’s aim is to compare pregnancy outcomes in multifetal gestations that were conceived spontaneously compared to in vitro fertilization (IVF). Few population-based studies have addressed this topic. Study design: This is a retrospective cohort study using the Health Care Cost and Utilization Project-Nationwide Inpatient Sample (HCUP-NIS) database. Our study cohort included 90,552 multifetal gestations conceived spontaneously and 3219 IVF conceptions, from 2008 to 2014, inclusively. Multivariate logistic regression analyses were performed comparing maternal and neonatal outcomes, whilst adjusting for confounding variables. Subject was conducted using ICD-9 codes for multifetal gestation: 651. X and 76.1 and ICD-9 code for IVF: 23.85. Each pregnancy was included once. Results and conclusion: IVF multifetal gestations had increased risk of pregnancy-induced hypertension (aOR 1.31, 95 % CI 1.20–1.43), gestational hypertension (aOR 1.21, 95 % CI 1.04–1.41), preeclampsia (aOR 1.31, 95 % CI 1.19–1.45), gestational diabetes (aOR 1.26, 95 % CI 1.13–1.41) and placenta previa (aOR 1.7, 95 % CI 1.32–2.19). IVF delivery outcomes were more likely complicated by cesarean section (aOR 1.21, 95 % CI 1.10–1.33), preterm premature rupture of membranes (aOR 1.33, 95 % CI 1.16–1.52), chorioamnionitis (aOR 1.71, 95 % CI 1.37–2.14), postpartum hemorrhage (aOR 1.44, 95 % CI 1.26–1.63) and transfusions (aOR 1.48, 95 %CI 1.26–1.74). IVF neonatal outcomes were more likely complicated by small for gestational age (aOR 1.26, 95 % CI 1.12–1.41) and congenital anomalies (aOR 1.82, 95 % CI 1.29–2.57). IVF was not found to increase risks of eclampsia, preterm delivery, operative vaginal delivery, hysterectomy, or intrauterine fetal demise.IVF increased the risk of pregnancy, delivery, and neonatal outcomes in multifetal pregnancies with risks increased from 20 % to 70 %. The role of infertility versus the need for IVF and the type of IVF protocol used should be further evaluated.